Proposition of the 3-block Perfume Exhibition Model: Using Technology on Turning Visible an Invisible Reality Such as Perfumes - Cândido, J. V.; Ferreira, P. A. (15th Iberian Conference on Information Systems and Technologies, 2020)
Perfumes are part of our daily life. They can be a possible way to express our beauty or they can bring to life some memories or they can be simply hygienical accessories. Hard to describe, impossible to see. Perfumes have some mystical aura above them. For the industry perspective, perfumes present a challenge that is how to turn visible such an invisible, intangible and mystical object. The lineup questions of this study seek to explore the artistic endeavor perfumes can display and the advantages of retrieving data to improve the exhibition and to develop new business models. To develop this theoretical, conceptual and exploratory study one must look at some of the scholars’ contributions to this subject and the fragrance exhibitions made to this day. Moreover, some empirical knowledge that helps to understand how value is perceived into modern perfumery is stated; such knowledge comes from previous exhibitions, either fragrance-related exhibitions or immersive experience exhibitions, and it can be studied and improved from one’s empirical experience. The study is aimed to serve as support for a Perfume Art Exhibitions and it will develop a role model for future olfactory art exhibitions. Sensorial experiences and the visitors’ embodiment are critical factors for the success of an exhibition; hence this article seeks to propose a new exhibition model, totally oriented for the visitors’ needs and expectations but also for the brands’ market research and segmentation efforts. The 3-block model can be used for both an exhibition and to a permanent art museum. This model is innovative because it enhances the artistic role of perfumes and it will get visitors to dive into perfumes, gaining vocabulary and exploring the “making of” perfumes.